A high thermal conductivity layered titanium-based composite material with continuous graphene structure and a preparation method thereof

CN120551401BActive Publication Date: 2026-11-03HARBIN INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510808443.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-06-17
Publication Date
2026-11-03
Estimated Expiration
2045-06-17

AI Technical Summary

Technical Problem

Existing titanium-based composite materials have low thermal conductivity and high interfacial thermal resistance in aerospace applications. Furthermore, the high content of reinforcing phases leads to brittleness and decreased mechanical properties, making it difficult to achieve a balance between high thermal conductivity and high strength.

Method used

By ablation of graphene paper to form a through-hole array, combined with overlapping titanium powder layers, a layered titanium-based composite material with a continuous graphene structure is prepared by vacuum hot pressing sintering, thus constructing an efficient and interconnected heat-conducting channel and achieving the directional alignment of graphene and titanium matrix.

Benefits of technology

It significantly improves the thermal conductivity of titanium-based composite materials while maintaining good tensile plasticity, expands the application range of materials, solves the problem of heat accumulation, and enhances the overall performance of materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120551401B_ABST
    Figure CN120551401B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of high thermal conductivity layered titanium-based composite with continuous graphene structure and its preparation method, belong to novel aerospace titanium alloy material preparation technical field.To solve the problem of large interface thermal resistance of titanium-based composite, poor heat conduction performance, the present application provides a kind of preparation method of high thermal conductivity layered titanium-based composite with continuous graphene structure, laser marking is formed on graphene paper Ablation form through-hole array, titanium powder layer and graphene paper with through-hole array are overlapped and laid in mold, obtain layered blank for powder metallurgy, vacuum hot-pressing sintering obtains high thermal conductivity layered titanium-based composite with continuous graphene structure.The present application constructs efficient and connected high-thermal-conductivity channel, while ensuring the effective connection of titanium matrix, significantly enhances the heat conduction capacity of titanium-based composite under the premise of maintaining lower graphene content, effectively solves the problem of heat accumulation encountered by component during service, local failure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of novel aerospace titanium alloy material preparation technology, and particularly relates to a high thermal conductivity layered titanium-based composite material with a continuous graphene structure and its preparation method. Background Technology

[0002] With the rapid development of the aerospace industry and continuous technological innovation, the performance requirements for materials used in hot-end components of aircraft surfaces are becoming increasingly stringent, especially in the pursuit of lightweight, heat resistance, and high strength. Titanium alloys, with their superior specific strength and modulus, excellent corrosion resistance, and high-temperature resistance, have become key materials in aerospace vehicle manufacturing. However, despite these advantages, titanium alloys face a bottleneck problem when applied to hot-end components of aerospace surfaces, such as aircraft aerodynamic control surfaces. During service, these components generate significant aerodynamic heat due to intense friction with high-speed airflow. Titanium alloys have a relatively low intrinsic thermal conductivity of only about 7 W / (m·K), meaning that the rapidly accumulated heat on the component surface is difficult to dissipate quickly through heat conduction. With a sharp increase in local temperature, the performance of titanium alloy materials will deteriorate significantly, and softening failure may even occur, seriously affecting the stability and safety of the aircraft.

[0003] The diverse lattice vibration modes of titanium metal lead to severe phonon scattering during transmission, while the low concentration of free electrons outside the nucleus of titanium atoms also affects its electronic thermal conductivity. To improve the thermal conductivity of titanium-based composites, it is necessary to introduce reinforcing phases with high thermal conductivity, such as diamond and graphene. Chen et al. prepared Ti64-based composites with diamond content exceeding 20 wt.% using directional energy deposition, which increased the room temperature thermal conductivity by approximately 200%. However, with increasing diamond content, the composite exhibited a problem of inverse strength and thermal conductivity. When the reinforcing phase content exceeded 40 wt.%, more defects were generated inside the composite, which not only caused a decrease in thermal conductivity but also impaired the mechanical properties of the composite.

[0004] Yan et al. added a large amount of graphene to titanium-based composites prepared by hot isostatic pressing, which significantly improved the thermal conductivity of the composites. However, the large amount of graphene introduced many defects, causing the composites to exhibit significant room-temperature brittleness. Yang et al. prepared titanium-based composites with low graphene content through ball milling and microwave sintering. However, due to the discontinuous distribution of graphene in the titanium-based composites and the severe interfacial reaction with titanium, the thermal conductivity of the titanium-based composites decreased slightly.

[0005] Currently, in titanium-based composites with high-content reinforcing phases designed based on thermal percolation theory, the reinforcing phases are typically randomly distributed within the matrix. This leads to low thermal conductivity of the reinforcing phases and poor matrix connectivity. Simultaneously, the numerous interfaces resulting from the disordered distribution of the reinforcing phases significantly increase the thermal resistance of the composites. Therefore, the increase in thermal conductivity of existing titanium-based composites is limited, and they essentially lack tensile plasticity. Furthermore, the thermal conductivity of highly thermally conductive second phases such as graphene, carbon nanotubes, and boron nitride nanosheets is directional, and current titanium-based composite fabrication techniques struggle to achieve directional distribution of these highly thermally conductive second phases, further reducing the thermal conductivity of the composites. Summary of the Invention

[0006] To address the issues of high interfacial thermal resistance and poor thermal conductivity in titanium-based composite materials, this invention provides a high thermal conductivity layered titanium-based composite material with a continuous graphene structure and its preparation method.

[0007] The technical solution of this invention:

[0008] A method for preparing a high thermal conductivity layered titanium-based composite material with a continuous graphene structure, comprising the following steps:

[0009] Step 1: Form an array of through holes on graphene paper by laser marking and ablation;

[0010] Step 2: In the mold, titanium powder layers and graphene paper with through-hole array obtained in Step 1 are laid in overlapping layers. Each layer is laid as one layer, and a total of 20 to 30 layers are laid to obtain a layered blank for powder metallurgy.

[0011] Step 3: Vacuum hot pressing sintering is performed on the layered blank obtained in Step 2 to obtain a high thermal conductivity layered titanium-based composite material with a continuous graphene structure.

[0012] Furthermore, the through-hole array in step one is an array of multiple through-hole structures arranged at a fixed interval, the diameter of the through-hole is 25~250μm, and the distance between two adjacent through-holes is 0.25~1mm.

[0013] Furthermore, the thickness of the graphene paper described in step one is 10~100μm.

[0014] Furthermore, the laser marking power in step one is 10~100W, the scanning speed is 30~500mm / s, and the number of scans is 1~3 times.

[0015] Furthermore, the thickness of the titanium powder layer in step two is 200~1000μm.

[0016] Furthermore, the titanium powder layer in step two is made of pure titanium powder or titanium alloy powder; the particle size of the pure titanium powder or titanium alloy powder is 15~53μm.

[0017] Furthermore, the titanium alloy powder is TC4 titanium alloy powder, TA15 titanium alloy powder, or Ti60 titanium alloy powder.

[0018] Furthermore, the vacuum degree of the vacuum hot pressing sintering described in step three is not higher than 10. -2 Pa, sintering temperature is 900~1300℃, pressure is 50MPa, and holding time is 1h.

[0019] Furthermore, the thickness of the layered titanium-based composite material obtained in step three is 2~50mm.

[0020] The present invention provides a high thermal conductivity layered titanium-based composite material with a continuous graphene structure, wherein the graphene content is 0.5~10 wt.%.

[0021] The beneficial effects of this invention are:

[0022] Based on the theory of thermally conductive networks, this invention utilizes highly thermally conductive graphene paper with oriented graphene sheets to construct efficient and interconnected high thermal conductivity channels in titanium-based composite materials through a layered configuration design. At the same time, the through-hole array on the graphene paper ensures effective connectivity of the titanium matrix, achieving the integration of high performance and structural function. This significantly enhances the thermal conductivity of titanium alloys, effectively solves the problem of heat accumulation encountered by components during service, and greatly expands the application range of titanium alloys.

[0023] This invention utilizes graphene paper with thicknesses of 20 μm and 50 μm to prepare 20-layer pure titanium-based layered titanium composites with graphene contents of 1.6 wt.% and 4 wt.%, respectively. Testing revealed that the thermal conductivity of these layered titanium composites reached 87.9 W / (m·K) and 139.0 W / (m·K), respectively, representing increases of 303% and 538% compared to the pure titanium matrix. This invention achieves a significant improvement in the thermal conductivity of layered titanium composites while maintaining a relatively low graphene content, overcoming the limitations of titanium composites in thermal conductivity. Simultaneously, the titanium composite prepared from 20 μm thick graphene paper retains nearly 5% tensile plasticity at room temperature, demonstrating excellent overall performance. Attached Figure Description

[0024] Figure 1 This is a side view of the layered blank obtained by overlapping titanium powder layers and graphene paper with through-hole array according to the present invention.

[0025] Figure 2 Micrograph of the longitudinal section of the layered titanium-based composite material prepared in Example 1;

[0026] Figure 3Micrograph of the longitudinal section of the layered titanium-based composite material prepared in Example 2;

[0027] Figure 4 A comparison of room temperature tensile stress-strain curves for pure titanium, layered titanium matrix composites prepared in Example 1 and Example 2. Detailed Implementation

[0028] The technical solution of the present invention will be further described below with reference to embodiments, but it is not limited thereto. Any modifications or equivalent substitutions to the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be covered within the protection scope of the present invention. In the following embodiments, the process equipment or apparatus not specifically specified are all conventional equipment or apparatus in the art. Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commercially available; unless otherwise specified, the technical means used in the embodiments of the present invention are all conventional means well known to those skilled in the art.

[0029] Example 1

[0030] This embodiment provides a high thermal conductivity layered titanium-based composite material with a continuous graphene structure and its preparation method.

[0031] The preparation steps of the layered titanium-based composite material in this embodiment are as follows:

[0032] Step 1: First, cut 20μm thick graphene paper to a suitable size. Then, use laser marking technology to ablate an array of through holes on the graphene paper. The laser marking power is 50W, the scanning speed is 200mm / s, and the number of scans is 2. The through hole array consists of multiple through hole structures arranged at a fixed interval. The diameter of the through hole is 0.25mm, and the distance between two adjacent through holes is 1mm.

[0033] The ablated pores on the graphene paper are used to allow the pure titanium matrix on both sides of the graphene paper to be interconnected during the subsequent preparation of composite materials, thereby improving the connectivity of the titanium matrix in the composite material.

[0034] Step 2: Lay a layer of pure titanium powder with a particle size of 15-53 μm in the mold, with a thickness of 500 μm. Then, lay a sheet of graphene paper with a perforated array obtained in Step 1 on top of the pure titanium powder layer. Continue to overlap and lay titanium powder layers and graphene paper with a perforated array obtained in Step 1, one layer per overlap, for a total of 20 layers, to obtain a layered blank for powder metallurgy. A side view of the layered blank obtained by the overlapping layup is shown below. Figure 1 As shown.

[0035] In this embodiment, pure titanium powder with a thickness of 15~53μm was selected so that the titanium powder could effectively fill the gaps in the laser-marked graphene paper, thereby achieving interconnection between the upper and lower titanium powder layers of the graphene paper and improving the matrix connectivity.

[0036] Step 3: Vacuum hot pressing sintering is performed on the layered blank obtained in Step 2. The vacuum degree of vacuum hot pressing sintering shall not exceed 10. -2 A layered titanium-based composite material with high thermal conductivity and a continuous graphene structure was obtained by sintering at 900℃, pressure of 50MPa, and holding time of 1h. The composite material had a thickness of 7mm.

[0037] The longitudinal section microstructure of the layered titanium-based composite material in this embodiment is as follows: Figure 2 As shown in the figure, the titanium powder layers on the top and bottom of the graphene paper are interconnected.

[0038] Example 2

[0039] This embodiment provides a high thermal conductivity layered titanium-based composite material with a continuous graphene structure and its preparation method.

[0040] The preparation steps of the layered titanium-based composite material in this embodiment are as follows:

[0041] Step 1: First, cut a 50μm thick graphene paper to a suitable size. Then, use laser marking technology to ablate the graphene paper to form a through-hole array. The through-hole array consists of multiple through-hole structures arranged at a fixed interval. The diameter of each through-hole is 0.25mm, and the distance between two adjacent through-holes is 1mm. In this embodiment, the laser marking power is 100W, the scanning speed is 50mm / s, and the number of scans is 3.

[0042] Step 2: Lay a layer of pure titanium powder with a particle size of 15~53μm in the mold, with a thickness of 1000μm. Lay a graphene paper with a through-hole array obtained in Step 1 on the pure titanium powder layer. Continue to lay titanium powder layers and graphene paper with through-hole array obtained in Step 1 in an overlapping manner. Each set is a layer, and a total of 20 layers are laid to obtain a layered blank for powder metallurgy.

[0043] Step 3: Vacuum hot pressing sintering is performed on the layered blank obtained in Step 2. The vacuum degree of vacuum hot pressing sintering shall not exceed 10. -2 A layered titanium-based composite material with high thermal conductivity and a continuous graphene structure was obtained by sintering at 900℃, pressure of 50MPa, and holding time of 1h. The composite material had a thickness of 7mm.

[0044] The longitudinal section microstructure of the layered titanium-based composite material in this embodiment is as follows: Figure 3 As shown in the figure, the titanium powder layers on the top and bottom of the graphene paper are interconnected.

[0045] Example 3

[0046] This embodiment provides a high thermal conductivity layered titanium-based composite material with a continuous graphene structure and its preparation method.

[0047] The preparation steps of the layered titanium-based composite material in this embodiment are as follows:

[0048] Step 1: First, cut a 30μm thick graphene paper to a suitable size. Then, use laser marking technology to ablate an array of through-holes on the graphene paper. The through-hole array consists of multiple through-hole structures arranged at a fixed interval. The diameter of each through-hole is 0.05mm, and the distance between two adjacent through-holes is 0.25mm. In this embodiment, the laser marking power is 50W, the scanning speed is 100mm / s, and the number of scans is 2.

[0049] Step 2: Lay a layer of pure titanium powder with a particle size of 15~53μm in the mold, with a thickness of 330μm. Lay a graphene paper with a through-hole array obtained in Step 1 on the pure titanium powder layer. Continue to lay titanium powder layers and graphene paper with through-hole array obtained in Step 1 in an overlapping manner. Each set is a layer, and a total of 30 layers are laid to obtain a layered blank for powder metallurgy.

[0050] Step 3: Vacuum hot pressing sintering is performed on the layered blank obtained in Step 2. The vacuum degree of vacuum hot pressing sintering shall not exceed 10. -2 A layered titanium-based composite material with high thermal conductivity and a continuous graphene structure was obtained by sintering at 900℃, pressure of 50MPa, and holding time of 1h. The composite material had a thickness of 7mm.

[0051] Example 4

[0052] This embodiment provides a high thermal conductivity layered titanium-based composite material with a continuous graphene structure and its preparation method.

[0053] The preparation steps of the layered titanium-based composite material in this embodiment are as follows:

[0054] Step 1: First, cut 80μm thick graphene paper to a suitable size. Then, use laser marking technology to ablate and form a through-hole array on the graphene paper. The through-hole array consists of multiple through-hole structures arranged at a fixed interval. The diameter of each through-hole is 0.1mm, and the distance between two adjacent through-holes is 0.5mm. In this embodiment, the laser marking power is 100W, the scanning speed is 50mm / s, and the number of scans is 3.

[0055] Step 2: Lay a layer of TC4 titanium alloy powder with a particle size of 15~53μm in the mold, with a thickness of 1000μm. Lay a graphene paper with a through-hole array obtained in Step 1 on the TC4 titanium alloy powder layer. Continue to overlap the titanium powder layer and the graphene paper with a through-hole array obtained in Step 1. Each set is a layer, and a total of 25 layers are laid to obtain a layered blank for powder metallurgy.

[0056] Step 3: Vacuum hot pressing sintering is performed on the layered blank obtained in Step 2. The vacuum degree of vacuum hot pressing sintering shall not exceed 10. -2 A layered titanium-based composite material with high thermal conductivity and a continuous graphene structure was obtained by sintering at a temperature of 1200℃, a pressure of 50MPa, and a holding time of 1h. The composite material had a thickness of 18mm.

[0057] Example 5

[0058] This embodiment provides a high thermal conductivity layered titanium-based composite material with a continuous graphene structure and its preparation method.

[0059] The preparation steps of the layered titanium-based composite material in this embodiment are as follows:

[0060] Step 1: First, cut 10μm thick graphene paper to a suitable size. Then, use laser marking technology to ablate an array of through-holes on the graphene paper. The through-hole array consists of multiple through-hole structures arranged at a fixed interval. The diameter of each through-hole is 0.025mm, and the distance between two adjacent through-holes is 0.25mm. In this embodiment, the laser marking power is 50W, the scanning speed is 300mm / s, and the number of scans is 1.

[0061] Step 2: Lay a layer of TA15 titanium alloy powder with a particle size of 15~53μm in the mold, with a thickness of 200μm. Lay a graphene paper with a through-hole array obtained in Step 1 on the TA15 titanium alloy powder layer. Continue to overlap the titanium powder layer and the graphene paper with a through-hole array obtained in Step 1. Each set is a layer, and a total of 50 layers are laid to obtain a layered blank for powder metallurgy.

[0062] Step 3: Vacuum hot pressing sintering is performed on the layered blank obtained in Step 2. The vacuum degree of vacuum hot pressing sintering shall not exceed 10. -2 A layered titanium-based composite material with high thermal conductivity and a continuous graphene structure was obtained by sintering at a temperature of 1200℃, a pressure of 50MPa, and a holding time of 1h. The composite material had a thickness of 6mm.

[0063] Example 6

[0064] This embodiment provides a high thermal conductivity layered titanium-based composite material with a continuous graphene structure and its preparation method.

[0065] The preparation steps of the layered titanium-based composite material in this embodiment are as follows:

[0066] Step 1: First, cut 100μm thick graphene paper to a suitable size. Then, use laser marking technology to ablate and form a through-hole array on the graphene paper. The through-hole array consists of multiple through-hole structures arranged at a fixed interval. The diameter of each through-hole is 0.15mm, and the distance between two adjacent through-holes is 0.4mm. In this embodiment, the laser marking power is 100W, the scanning speed is 50mm / s, and the number of scans is 5.

[0067] Step 2: Lay a layer of Ti60 titanium alloy powder with a particle size of 15~53μm in the mold, with a thickness of 1000μm. Lay a graphene paper with a through-hole array obtained in Step 1 on the TA15 titanium alloy powder layer. Continue to overlap the titanium powder layer and the graphene paper with a through-hole array obtained in Step 1. Each set is a layer, and a total of 20 layers are laid to obtain a layered blank for powder metallurgy.

[0068] Step 3: Vacuum hot pressing sintering is performed on the layered blank obtained in Step 2. The vacuum degree of vacuum hot pressing sintering shall not exceed 10. -2 A high thermal conductivity layered titanium-based composite material with a continuous graphene structure and a thickness of 14 mm was obtained by sintering at a temperature of 1300℃, a pressure of 50MPa, and a holding time of 1h.

[0069] The thermal conductivity and graphene content of the layered titanium-based composite materials prepared in Examples 1-6 were tested respectively, and the results are shown in Table 1.

[0070] Table 1

[0071]

[0072] As can be seen from the data comparison in Table 1, the present invention achieves a significant improvement in thermal conductivity at a low graphene content, breaking through the thermal conductivity bottleneck of titanium-based composite materials.

[0073] The room temperature tensile plasticity of pure titanium material, the layered titanium matrix composites prepared in Example 1 and Example 2 were tested respectively, and the results are as follows: Figure 4 As shown, the titanium-based composite material prepared from 20μm thick graphene paper still maintains close to 5% tensile plasticity at room temperature, demonstrating good comprehensive performance.

[0074] The method for preparing layered titanium-based composite materials provided by this invention offers high flexibility and designability, allowing for precise control of the thickness of the graphene paper, the thickness of the titanium powder layer, and the number of overlapping layers according to the actual mechanical performance requirements of the product. This preparation method not only optimizes the overall performance of the material but also greatly expands its application areas.

Claims

1. A method for preparing a high thermal conductivity layered titanium-based composite material with a continuous graphene structure, characterized in that, The steps are as follows: Step 1: A through-hole array is formed by laser marking on graphene paper with a thickness of 10~100μm. The through-hole array is an array of multiple through-hole structures arranged at a fixed interval. The diameter of the through-hole is 25~250μm, and the distance between two adjacent through-holes is 0.25~1mm. The laser marking power is 10~100W, the scanning speed is 30~500mm / s, and the number of scans is 1~3. Step 2: In a mold, titanium powder layers with a thickness of 200~1000μm are interleaved with graphene paper with through-hole array obtained in Step 1. Each interleaving is considered one layer, and a total of 20~30 layers are laid to obtain a layered blank for powder metallurgy. The titanium powder layer is made of pure titanium powder or titanium alloy powder; the particle size of the pure titanium powder or titanium alloy powder is 15~53μm. Step 3: Vacuum hot pressing sintering is performed on the layered blank obtained in Step 2. The vacuum degree of the vacuum hot pressing sintering is not higher than 10. -2 A high thermal conductivity layered titanium-based composite material with a continuous graphene structure was obtained by sintering at a temperature of 900~1300℃, a pressure of 50MPa, and a holding time of 1h.

2. The method for preparing the high thermal conductivity layered titanium-based composite material with a continuous graphene structure according to claim 1, characterized in that, The titanium alloy powder is TC4 titanium alloy powder, TA15 titanium alloy powder, or Ti60 titanium alloy powder.

3. The method for preparing the high thermal conductivity layered titanium-based composite material with a continuous graphene structure according to claim 2, characterized in that, The thickness of the layered titanium-based composite material obtained in step three is 2~50mm.

4. A high thermal conductivity layered titanium-based composite material with a continuous graphene structure prepared by the preparation method according to any one of claims 1-3, characterized in that, The graphene content is 0.5~10 wt.%.

Citation Information

Patent Citations

  • Graphite-copper laminar composite material and preparing method thereof

    CN109175356A

  • Preparation method of layered graphene / titanium composite material

    CN113619220A